Prevalence, patterns of addictions and its impact on mental health among undergraduate medical students in Belagavi: a cross-sectional study - Periyasamy, Manjula; Chingale, Ashwini L. (International Journal Of Community Medicine And Public Health, 2025)
Background: Undergraduate medical students are vulnerable to various forms of addiction owing to academic stress and lifestyle. Both substance use and internet addiction are recognized as determinants of psychological morbidity, potentially affecting their academic performance. This study aimed to assess the prevalence and patterns of substance use and internet addiction and their impact on mental health among undergraduate medical students in Belagavi. Methods: A cross-sectional study was conducted among 498 undergraduate medical students in November–December 2024. Data were collected using a structured, pretested questionnaire which included socio-demographic data, ASSIST (Alcohol, Smoking and Substance Involvement Screening Test), AUDIT (Alcohol Use Disorders Identification Test), GHQ-28 (General Health Questionnaire-28) and Young’s Internet Addiction Test. Statistical analysis was performed using SPSS v25.0 with association assessed using the chi-square test with a significant level (p<0.05) Results: Most participants (91.4%) were aged 19–25 years, with 57.2% males. Internet addiction was found in 58.6% (mild–moderate) and 0.4% (severe). Substance use was low sedatives (4.4%), inhalants (0.6%) and risky alcohol use in 23.9% of the participants. Psychological distress was mild in 16.9% and moderate in 2%. Tobacco, alcohol use and internet addiction were significantly associated with anxiety and depression (p<0.001). Conclusions: Internet addiction and substance use though varying in prevalence, A significant proportion of medical students had internet and substance-related addictions, with significant mental health effects. Targeted interventions such as counseling, stress management and digital hygiene training are warranted to mitigate these risks.